Pengaruh Investment Knowledge, Motivasi Investasi dan Manfaat Investasi Terhadap Manajemen Keuangan Pribadi Pegawai UINFAS Bengkulu - Lestari, Sri; Arisandy, Yosy; Hanif, Padlim (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2025)
This study aims to analyze the influence of investment knowledge, motivation, and investment benefits on personal financial management of UINFAS Bengkulu employees. This study uses a quantitative approach with primary data collection techniques through questionnaires distributed to 80 respondents. Data were analyzed using multiple linear regression with the help of SPSS software. he results of the study indicate that partially, investment knowledge has a positive and significant effect on personal financial management, with a significance value of 0.009 (<0.05). Likewise, investment motivation also has a positive and significant effect partially with a significance level of 0.000. On the other hand, investment benefits do not show a significant effect partially, because they have a significance value of 0.127 (>0.05). However, simultaneously the three variables—investment knowledge, investment motivation, and investment benefits—have a positive and significant effect on personal financial management of UINFAS Bengkulu employees. This finding indicates that although investment benefits do not have an effect individually, these variables still make a positive contribution to the overall model. The results of this study provide implications that increasing investment knowledge and motivation is very important in supporting better personal financial management in higher education institutions.